Montmorillonite K10-catalyzed synthesis of N-fused imino-1, 2, 4-thiadiazolo isoquinoline derivatives. Issue 11 (3rd June 2018) - Chacko, Priya; Shivashankar, Kalegowda
ABSTRACT: A novel synthesis of N -fused imino-1, 2, 4-thiadiazolo derivatives is described. This approach involves the inexpensive, nontoxic, recoverable, and easy to handle montmorillonite K10 that catalyzes the coupling of 3-aminoisoquinolines and phenylisothiocyanates to afford the N -fused imino-1, 2, 4-thiadiazolo isoquinoline motifs in exemplary yields. The main attractions of this synthetic strategy were simple procedure and excellent yields. GRAPHICAL ABSTRACT: